PEMIKIRAN POLITIK HASAN AL-BANNA - Dewi, Rusmala (Nurani, 2015)
Abstract: Hasan al Banna, one of Islamic prominent figures,was born at the end of 20 tahun century. His ideas andmovement together with ikhwanul Muslimin had arousedfighting spirit of Islamic society in order not be left behind.Returning to the life inspired by al-quran and as sunnah is themission of the movement led by Hasan al Banna. Although thisIslamic renewal figure had passed away, his thoughts still existin Islamic society’s life. Therefore, Hasan al-Banna’s thoughtswill be discussed in this article especially his political ideas .ملخص: ولد حسن البنا، واحدة من الشخصیات البارزة الإسلامیة ، في نھایة القرن20 . قد أفكاره و الحركة جنبا إلى جنب مع" الإخوان والمسلمین" أثار الروح القتالیةللمجتمع الإسلامي لكي لا أن تترك وراءھا. وبالعودة إلى الحیاة مستوحاة من آل القرآنو السنة كما ھي مھمة الحركة التي یقودھا حسن البنا. على الرغم من أن ھذا الرقمالتجدید الإسلامي قد وافتھ المنیة، أفكاره لا تزال موجودة في الحیاة المجتمع الإسلامي.لذلك، سیتم مناقشة الأفكار حسن البنا في ھذه المقالة خاصة أفكاره السیاسیةKata Kunci: Hasan al-Banna, Islam dan Politik.